Methods of molecular analysis in the life sciences - Hofmann, Andreas; Simon, Anne; Grkovic, Tanja; Jones, Malcolm (Professor of veterinary biology and parasitology) (UK: Cambridge University Press, 2014)
"Delivering fundamental insights into the most popular methods of molecular analysis, this text is an invaluable resource for students and researchers. It encompasses an extensive range of spectroscopic and spectrometric techniques used for molecular analysis in the life sciences, especially in the elucidation of the structure and function of biological molecules. Covering the range of up-to-date methodologies from everyday mass spectrometry and centrifugation to the more probing X-ray crystallography and surface-sensitive techniques, the book is intended for undergraduates starting out in the laboratory and for more advanced postgraduates pursuing complex research goals. The comprehensive text provides strong emphasis on the background principles of each method, including equations where they are of integral importance to the individual techniques. With sections on all the major procedures for analysing biological molecules, this book will serve as a useful guide across a range of fields, from new drug discovery to forensics and environmental studies"--Provided by publisher.
Machine generated contents note: Foreword Robert Huber; Preface; Lists of dimensions and constants; 1. Introduction; 2. Spectroscopic methods; 3. Structural methods; 4. Physical methods; 5. Surface-sensitive methods; References; Index.
Includes bibliographical references (pages 203-213) and index.
Keywords: Biochemical Processes; Chemistry Techniques, Analytical